2014
DOI: 10.1525/abt.2014.76.9.6
|View full text |Cite
|
Sign up to set email alerts
|

How Do Small Things Make a Big Difference? Activities to Teach about Human–Microbe Interactions

Abstract: Recent scientific studies are providing increasing evidence for how microbes living in and on us are essential to our good health. However, many students still think of microbes only as germs that harm us. The classroom activities presented here are designed to shift student thinking on this topic. In these guided inquiry activities, students investigate human–microbe interactions as they work together to interpret and analyze authentic data from published articles and develop scientific models. Through the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The implementation of SJG and JG in Embryology course plays a direct role in improving cooperative skills and student achievement (Haviz, 2015(Haviz, , 2016. The principles of cooperative learning that are applied in small groups (Bellanca et al, 2010;Slavin, 2014), provide more space for students to take on the role and work together as a learner (Cetindamar & Hopkins, 2008;Jasti et al, 2014). Social interactions that occur in learning activities affect how students master the material (Pang, Lau, Seah, Cheong, & Low, 2018;Shin, Lee, & Ha, 2017).…”
Section: Figure 2 Cooperative Of Student Skills On Embryology Coursementioning
confidence: 99%
See 1 more Smart Citation
“…The implementation of SJG and JG in Embryology course plays a direct role in improving cooperative skills and student achievement (Haviz, 2015(Haviz, , 2016. The principles of cooperative learning that are applied in small groups (Bellanca et al, 2010;Slavin, 2014), provide more space for students to take on the role and work together as a learner (Cetindamar & Hopkins, 2008;Jasti et al, 2014). Social interactions that occur in learning activities affect how students master the material (Pang, Lau, Seah, Cheong, & Low, 2018;Shin, Lee, & Ha, 2017).…”
Section: Figure 2 Cooperative Of Student Skills On Embryology Coursementioning
confidence: 99%
“…(Oakes, Hegedus, Ollerenshaw, Drury, and Ritchie, 2019) found that the jigsaw method increases knowledge about anatomy by involving group work, peer-led learning, minimal supervision, and leads to increased student performance and learning motivation. While other research also reports that various biology topics such as ecology (Asshoff, Düsing, Winkelmann, & Hammann, 2019;Smith & Chang, 2005), microbiology (Jasti, Hug, Waters, & Whitaker, 2014), anatomy (Koprowski & Perigo, 2000), biology developmental (Haviz, 2015) that are taught with jigsaw have a positive impact on students' understanding, interest in learning, and thinking ability including cognitive (Bennett, 2016) and metacognitive awareness (Palennari, 2016).…”
Section: Introductionmentioning
confidence: 99%